Music Based Metaheuristic Methods for Constrained Optimization - Altay, Elif Varol; Alatas, Bilal (Ieee, 2018)
In this work, music based metaheuristic search methods have been collected and discussed for the first time Harmony Search Algorithm (HS), which are the most well-known music based optimization algorithms, its variants, Method of Musical Composition Algorithm (MMC), and Melody Search Algorithm (MSA) have been examined in detail and their performance tests in terms of different statistical metrics have been carried out with constrained G-suit functions and the results have been demonstrated comparatively. These algorithms are relatively interesting and novel and many efficient versions of them can be proposed and adopted for many types of nonlinear complex problems.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: Metaheuristic Algorithms; Music Based Optimization Algorithms; Constrained Optimization